Kajian Sistematis Kemandirian Belajar terhadap Kemampuan Pemecahan Masalah Matematis Siswa SMP - Anna Tasya Enjelina Br Tumanggor; I Nyoman Budayana; I Made Suarsana (Institut Nalanda, 2026)
This study aims to examine the relationship between self-regulated learning and mathematical problem-solving skills among junior high school students through a systematic review of recent literature. The study employed a descriptive qualitative approach by analyzing scientific articles published between 2021 and 2025. Relevant articles were collected from databases such as Google Scholar, Scopus, ERIC, and ScienceDirect using keywords related to self-regulated learning and mathematical problem-solving. Based on predetermined inclusion and exclusion criteria, 10 articles were selected for analysis. The findings indicate that self-regulated learning plays a significant role in improving students’ mathematical problem-solving abilities. Students with strong self-regulation tend to be more effective in understanding problems, selecting appropriate solution strategies, carrying out problem-solving procedures systematically, and evaluating their results. Furthermore, student-centered learning approaches have been shown to foster self-regulated learning and enhance problem-solving performance. However, the reviewed studies reveal that most junior high school students still demonstrate low to moderate levels of mathematical problem-solving skills, particularly when dealing with non-routine problems. These findings highlight the need for innovative and student-centered instructional strategies that encourage learning autonomy and active participation. This study provides both theoretical insights and practical recommendations for improving mathematics education at the junior high school level.